Pengaruh Senam Kaki Terhadap Penurunan Resiko Neuropati Perifer Dengan Skor Diabetic Neuropathy Examination Pada Pasien Diabetes Melitus Tipe 2 Di Puskesmas Sibela Kota Surakarta - Desy Indah Ratnawati; Insiyah Insiyah ((JKG) Jurnal Keperawatan Global, 2017)
Abstract : Foot Gymnastics, Diabetic Neuropathy Examination Score. Peripheral neuropathy is one of chronic complications frequently found in diabetes mellitus case. The risks of the diabetic patient with peripheral neuropathy face included repeated infection, refractory ulcer and finger and foot amputation. This condition requires an easy and cheaper primary treatment, foot gymnastic. This research aimed to find out the effect of foot gymnastic on the decreased peripheral neuropathy with diabetic neuropathy examination score in patients with type 2 diabetes mellitus in Puskesmas (Public Health Center) Sibela in Surakarta City. The Research Methods could be used design using quasy experiment design with one group method pre test – post test. The samples are 30 participant of foot gymnastics at Puskesmas Sibela in February until April 2015. This research use paired t test in order to know risk decrease of peripheral neuropathy by diabetic neuropathy examination score. The results could from 30 respondents is obtained a mean diabetic examination neuropathy score before foot gymnastics was 7,67 with a standard deviation of 2,63 and after foot gymnastics was 5,37 with a standard deviation of 2,632. From the paired t test analysis was obtained p = 0,001 (p<0,05). Conclusion existence of influence foot gymnastic againts a decreased risk of peripheral neuropathy based on diabetic neuropathy examination scores. Suggestion for the next research measurement diabetic neuropathy examination scores for 3 to 6 months to obtain optimal result.